SUSTAINABILITY IN SUPPLY CHAINS: STRATEGIES AND PRACTICES FOR A GREENER FUTURE - Makprang, Kittinun (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2024)
Purpose – The purpose of this study is to investigate the critical importance of integrating sustainability practices into supply chain management. It aims to explore strategies and best practices that businesses can adopt to mitigate environmental challenges, reduce greenhouse gas emissions, and transition towards greener supply chains. Implications – The integration of sustainability into supply chain management has far-reaching implications for businesses, the environment, and society. By adopting sustainable practices, organizations can enhance their brand reputation, increase customer loyalty, achieve cost savings, improve risk management, foster innovation, and gain a competitive advantage. Additionally, the adoption of green supply chain practices contributes to environmental conservation, resource efficiency, and the mitigation of climate change impacts. Originality/Value – This study offers a comprehensive analysis of sustainable supply chain practices, with a particular focus on Thailand's manufacturing sector. It provides valuable insights into the challenges and opportunities associated with implementing sustainability strategies across various industries. The research highlights best practices, case studies, and recommendations tailored to the Thai context, enabling businesses to navigate the transition towards greener supply chains effectively. Furthermore, the study emphasizes the significance of Thailand's sustainability efforts in influencing global standards and positioning the nation as a leader in responsible manufacturing practices.